PENGARUH MEDIA POWERPOINT INTERAKTIF TERHADAP KEMAMPUAN KOGNITIF SISWA KELAS V PADA MATERI SISTEM PENCERNAAN MANUSIA DI SDN BANJARSARI 3 - Siti Amaliah; Amat Hidayat; Ahmad Mubarok; Aditya Rachman; Suganda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research was motivated by the low cognitive abilities of students, which have an impact on low learning outcomes. The aim of this study is to determine the effect of interactive PowerPoint learning media on the cognitive abilities of fifth-grade students in the human digestive system material at SDN Banjarsari 3. This research uses a quasi-experimental method with a Non-Equivalent Control Group Design. Data collection techniques were carried out through tests. Data analysis was conducted using prerequisite tests, hypothesis testing, and Effect Size. Based on the results of the t-test for the pretest, the significance value was 0.981 > 0.05, so H₀ is accepted. This means there is no significant difference in the initial cognitive abilities of the two groups. The posttest t-test results showed a significance value of 0.002 < 0.05, so H₀ is rejected. This indicates a significant difference between the experimental group and the control group. Furthermore, the Effect Size test results obtained a Cohen's d value of 1.002714, which is classified as high. It can be concluded that interactive PowerPoint learning media significantly influence the improvement of students' cognitive abilities.